Assistance in Learning the Quran Using Snake and Ladder Game Media at LPQ Keblukan Village, Kaloran District, Temanggung Regency - Fatijroh, Ibif; Sholehah, Ida Hidayatu; Nurrahma, Mita Amelia; Fadhir, Ahmad Al; Triana, Jupit; Pratama, Bagas Yoga; Fatchudin, Achmad; Ramadhani, Ekawati; Santika, Elsa Sopia; Nona, Nadya Noermala; Kwee, Saniayuen; Akbar, Givo Al; Aqil, Mukhamad Sa'id; Adi, Nugraho Prasetya (Society : Jurnal Pengabdian Masyarakat, 2025)
This study aims to describe the Qur'an learning assistance program using snake and ladder game media in LPQ Keblukan Village, Kaloran District, Temanggung Regency. This assistance was held to increase the understanding of the Qur'an and tajweed for LPQ students in Keblukan Village. This study uses a descriptive qualitative method. The researcher will collect qualitative data on existing mentoring practices, as well as contextual factors that affect Qur'an learning in the area.The Qur'an learning assistance program with the Iqra method and snake and ladder game media at LPQ Keblukan Village has proven to be effective in improving the ability to read and understand the Qur'an in children. This activity lasted for 2 weeks and involved students of the Community Service Lecture (KPM) of the University of Qur'an Sciences (UNSIQ). The results of the evaluation showed that this program succeeded in increasing children's learning motivation and participation in learning the Qur'an. Therefore, this program can be an example of the development of an effective and attractive Qur'an literacy program for children.